Implementation Of New Energy In Monitoring The Design And Construction Of Plant Watering Systems - Jeica Sampe Rante; yoffi Andinata (Yayasan Sinergi Multidimensi Kreatif, 2024)
Watering plants, especially orchids, requires special attention as these plants have an air humidity limit between 60-80% RH and an ambient temperature between 18–34°C. Improper watering can cause orchid plants to become too moist or dry. In Baru Village, East Jakarta, the one million orchids program faces challenges because watering is still done manually without humidity and temperature control. With about 200 pots of orchids to be watered daily, this process relies heavily on human labor.This service activity aims to implement a microcontroller-based automatic watering system for orchid plants in Baru Village. The system uses a DHT22 sensor to detect the humidity and ambient temperature of the plant. With a microcontroller, a humidity parameter of 60% RH and a maximum temperature of 33°C can trigger the activation of the pump relay. A battery-powered 12 Volt DC pump is used for watering, with hoses and nozzle sprayers that spray water in a mist to reach the entire plant. The device operates on its own energy from a solar panel with a capacity of 30 Wp. The results of the activity show that the device works automatically at a temperature of 33°C and a minimum humidity of 60% RH, with a watering frequency of about 2-3 times within 6 hours. Charging the battery from the solar panel works well, reaching a maximum voltage of 14.6 Volts.